Approaches to learning and contract cheating: exploring the mediating roles of authorship perceptions - Zhang, Yinxia; Ni, Fengqin (Studies in higher education (Dorchester-on-Thames), 2025)
As an undesired learning behavior, contract cheating has its roots in college students' difficulties in engaging in a challenging written assessment. To better understand this process, the study collects multicampus survey data from 910 Chinese undergraduates to explore the effects of deep and surface approaches to learning on contract cheating, focusing on the mediating roles of authorship perceptions. The authorship perceptions are measured with three subfactors: understanding authorship and plagiarism (UAP), authorial approach to writing (AAW), and incorporating others' writing (IOW). Structural equation modeling (SEM) reveals a notable positive direct effect of the surface approach to learning on contract cheating and an insignificant direct effect of the deep approach. The results further report significant indirect effects of both deep and surface approaches to learning on contract cheating via UAP and IOW, while the indirect effects via AAW are both insignificant. These results highlight the importance of providing formal and continuous pedagogical support to enhance their learning, particularly academic writing, in inhibiting contract cheating.